Shaming for tax enforcement: Evidence from a new policy - Nadja Dwenger; Lukas Treber (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Can public shaming increase tax compliance through social pressure? Many tax authorities make ample use of public shaming. However, empirical evidence from outside the laboratory on how a new shaming law affects overall compliance is lacking. We provide the first evidence from the field, exploiting comprehensive administrative tax data and the introduction of a novel naming-and-shaming policy in Slovenia in 2012. The policy aims to reduce outstanding tax debt among the self-employed and corporations. Our empirical strategy exploits the variation across taxpayers in ex ante exposure to the shaming policy. We find that taxpayers reduce their tax debt by 8.5% to avoid shaming, particularly in industries where reputational concerns are likely to be important. The publication of the first naming-and-shaming list further reduces tax debt among shamed taxpayers because of social learning. This effect, however, is marginal in terms of revenue and tapers off quickly.
urn:nbn:de:bsz:100-opus-15260
Keywords: H26; D1; K34; K42; Z13; 330; compliance; tax debt; shaming; enforcement; social image concerns; penalty